2021
DOI: 10.3389/fsurg.2021.656249
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infections Are Associated With Higher Blood Loss and Open Access in General Thoracic Practice

Abstract: Background: Surgical site infections (SSIs) are the most costly and second most frequent healthcare-associated infections in the Western world. They are responsible for higher postoperative mortality and morbidity rates and longer hospital stays. The aim of this study is to analyze which factors are associated with SSI in a modern general thoracic practice.Methods: Data were collected from our department's quality database. Consecutive patients operated between January 2014 and December 2018 were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…It declined consistently throughout the observation period, which could probably be explained by improvements in surgical techniques and equipment. The observed association between blood loss and infection rates was observed previously by other authors [51].…”
Section: All Patientssupporting
confidence: 88%
“…It declined consistently throughout the observation period, which could probably be explained by improvements in surgical techniques and equipment. The observed association between blood loss and infection rates was observed previously by other authors [51].…”
Section: All Patientssupporting
confidence: 88%
“…Many studies have shown that compared with traditional open surgery, minimally invasive surgery (MIS) represented by laparoscopic or thoracoscopic, endoscopic, and robotic-assisted surgery has significantly reduced the risk of SSI. [2][3][4][5] However, there is little evidence for this in thoracic surgery. Over the last two decades, robotic-assisted thoracic surgery (RATS) is changing the concept and mode of MIS in general thoracic surgery practice, especially in pulmonary lobectomy for early-stage NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasingly complex types of surgery, combined with the long‐term use of hormone, neoadjuvant therapy, previous history of thoracic surgery or trauma, the risk of pulmonary complications can be increased. Many studies have shown that compared with traditional open surgery, minimally invasive surgery (MIS) represented by laparoscopic or thoracoscopic, endoscopic, and robotic‐assisted surgery has significantly reduced the risk of SSI 2–5 . However, there is little evidence for this in thoracic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…SSI prolongs the hospital length of stay (LOS) and increases the readmission rate and healthcare costs ( 5 ). Multiple approaches have been advocated to lower SSI, including adequate bowel preparation, appropriate skin preparation, prophylactic antibiotics, intraoperative maintenance of normothermia, oxygenation, tissue microcirculation perfusion, normoglycemia, use of incision protectors and incision irrigation technique ( 6 , 7 ). Among these methods, conclusions on incision irrigation remain controversial.…”
Section: Introductionmentioning
confidence: 99%